Seasonality of female reproductive cycles in the neotropical aquatic snake, Helicops pastazae (2017)
Reproductive cycles of snakes have a great variability in timings and may be influenced by biotic or abiotic factors. For the Neotropical region, where seasonal variation in temperature is minimum, we hypothesize that the reproductive cycle of snakes is mostly influenced on the precipitation pattern of the region. The reproductive cycle of the colubrid aquatic snake, Helicops pastazae, was studied through monthly examination of gonadal dissections. We investigated female population in a mountainous region of Colombia with seasonal precipitation patterns. Other aspects of the reproductive biology such as sexual dimorphism, sexual size of maturity, clutch size, and litter size was also investigated. Males and females were found during all the year, with a higher encounter during the dry season. Recruitment of neonates was during the low rainfall period and the dry season. Sexual dimorphism was recorded in males with larger tails than females, and females with a wider midbody width than males. There was no significant difference between head length and head width among both sexes. Females have a discontinuous seasonal synchronic population, with a peak in reproductive activity during the period of high rainfall and ovipositioning of eggs occurring during the low rainfalls or dry season. We suggest the reproductive activity of the population studied is highly influenced by the rainfall patterns of the region